Bipolar Electric Field Pulses in the Martian Magnetosheath and Solar Wind; Their Implication and Impact Accessed by System Scale Size. Issue 7 (14th July 2022) - Thaller, Scott A.; Andersson, Laila; Schwartz, Steven J.; Mazelle, Christian; Fowler, Chris; Goodrich, Katherine; Newman, David; Halekas, Jasper; Pilinski, Marcin D.; Pollard, Matthew
Abstract: The scale size of the plasma boundary region between the sheath and ionosphere in the Martian system is often similar to the gyro‐radii of sheath protons, ∼200 km. As a result, ion energization via kinetic structures may play an important role in modifying the ion trajectories and thus be important when evaluating the large‐scale dynamics of the Martian system. In this paper, we report observations made with the MAVEN Langmuir Probe and Waves instrument of solitary bipolar electric field structures, and assess their potential role in ion energization in the Martian system. The observed structures appear as short duration (∼0.5 ms) bipolar electric field pulses of ∼1–25 mV/m, and are frequently observed in the upstream solar wind and inside the sheath. The study presented in this paper suggests that the bipolar electric field structures observed at Mars have an average electrostatic potential drop of ∼0.07 V. The estimated upper rate at which these structures could further energize the protons is estimated, assuming the protons gain the full 0.07 eV, to be ∼0.13 eV per gyration, or a change in proton energy of ∼0.3%, and a corresponding change in the gyroradius of ∼0.3 km. These numbers imply that to first order the bipolar structures are not a significant source of ion energization in the Martian magnetosheath. Key Points: The direct observation of bipolar electric field structures in Mars' sheath and solar wind, with durations of ∼0.5 ms and amplitudes ∼1–25 mV/m The bipolar structures have associated electric potentials of ∼0.002–2 V, ∼0.07 V on average The bipolar structures do not significantly impact sheath plasma through proton energization